2004
DOI: 10.1081/jcmr-120038528
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Wall Motion Abnormalities Found in Healthy Subjects by Cardiovascular Magnetic Resonance Imaging and Characterized with a New Segmental Model

Abstract: Right ventricular wall motion abnormalities are one of the criteria for the diagnosis of arrhythmogenic right ventricular cardiomyopathy. However, our findings indicate that they may also be seen around the insertion of the moderator band in healthy subjects, so that the significance of their presence at this site in patients undergoing diagnostic investigations for this disease should be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 18 publications
0
39
1
2
Order By: Relevance
“…Frequent sites for regional RV wall motion abnormality in ARVC include the basal and mid segments of the free wall, the inferior wall, including the acute angle of the RV, and the RVOT (12) (Fig 1) (Movies 1, 2 [online]). However, the findings from studies performed by Sievers et al (39) and Fritz et al (40) showed a high prevalence of subjective regional RV wall motion abnormality at cardiac MR imaging in healthy volunteers. The most frequent site of apparent abnormality, which was seen in 79% of the healthy volunteers, was at the insertion site of the moderator band in the apicolateral wall (Fig 9) (Movie 5 [online]).…”
Section: Apicolateral Bulgecontrasting
confidence: 43%
“…Frequent sites for regional RV wall motion abnormality in ARVC include the basal and mid segments of the free wall, the inferior wall, including the acute angle of the RV, and the RVOT (12) (Fig 1) (Movies 1, 2 [online]). However, the findings from studies performed by Sievers et al (39) and Fritz et al (40) showed a high prevalence of subjective regional RV wall motion abnormality at cardiac MR imaging in healthy volunteers. The most frequent site of apparent abnormality, which was seen in 79% of the healthy volunteers, was at the insertion site of the moderator band in the apicolateral wall (Fig 9) (Movie 5 [online]).…”
Section: Apicolateral Bulgecontrasting
confidence: 43%
“…32 A CMR study demonstrated a 93.1% prevalence of RV wall motion abnormalities in healthy subjects, including areas of apparent dyskinesia (75.9%) and bulging (27.6%). 33 All these data indicate that conventional CMR may lead to misdiagnosis of ARVC by showing equivocal morphofunctional RV abnormalities. This is in keeping with our findings showing, at best, moderate agreement (Ͻ0.61) between abnormal wall motion areas and scars for all RV regions, when comparing wall motion abnormalities identified by cine-CMR with both DCE and EAS ( Figure 5).…”
Section: Rv Dce Findingsmentioning
confidence: 99%
“…www.cardiologyjournal.org around the moderator band insertions remains difficult by MRI [15,16]. Emerging new echocardiographic techniques, specifically three dimensional (3D) RV echocardiography and tissue deformation imaging, may increase the performance of echocardiography, overcoming the previously mentioned shortcoming of conventional RV echocardiography [17,18].…”
mentioning
confidence: 99%